Application of Librarian Profession Interpersonal Communication in Influencing Library Existence - Rahima Husna; Restiana Restiana; Putri Lestari; Adha Rahimi; Kartini Kartini (Penerbit Jurnal Indonesia, 2022)
Communication is important in determining the ideal quality of library services, especially interpersonal communication. Interpersonal communication in the library occurs between librarians and library users. Librarians must have interpersonal skills to create good communication and not offend others. This study aims to determine the effect of librarian interpersonal communication on the existence of the library. In this study the authors used qualitative methods. The data collection technique is by conducting a document review or literature review. The existence of an open attitude, an attitude of empathy and an attitude that prioritizes the satisfaction of library users becomes a reference for increasing the existence of the library. Therefore, a librarian is needed to be able to develop his skills in the field of interpersonal communication. Therefore, the librarian is a professional profession and must know the library knowledge in depth. Thus, through communication the librarian can change the image and improve the existence of the library.